Coastal Litter and Surf Community Stewardship in Selected Surf Areas of Kuta, Canggu, and Uluwatu, Bali - Zion Pierson Medal; Frestika Dwinanda Situmeang (Journal of Marine Research, 2026)
Visible coastal litter remains a concern in Bali’s coastal areas, especially where tourism, marine ecosystems, and surfing activities intersect. This study examines visible coastal litter and the potential role of surf communities in supporting coastal environmental responsibility in selected surf-related areas in Kuta, Canggu, and Uluwatu. Using an exploratory qualitative case study, data were drawn from field observations, beach cleanup participation notes, contextual field notes, and relevant literature. The field records documented single-use plastics, food and beverage packaging, and mixed waste within different site-specific contexts, while organic or natural material was recorded separately as a contextual condition. At Kuta Beach, litter was documented around visitor-use and beach-access areas. At Batu Bolong Beach, debris was observed near shoreline, surf-access, and drainage- or river-connected zones. At Suluban Beach, localized litter was documented around surf-access and coastal recreation areas. These observed litter patterns suggest that coastal litter may be associated with beach-based consumption, tourism activity, rainfall-related runoff, drainage pathways, and land-based waste movement. Surf communities may contribute through cleanups, plastic reduction, peer education, social media communication, and local advocacy, but these actions require support from waste infrastructure, policy enforcement, producer responsibility, and sustainable tourism governance.